Development of Smart Beater and Pole Base Kasti Ball Game for Elementary School - Karsam Karsam; Ade Rahmat; Muhammad Suhairi (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. Development of batting equipment adapted to the developmental characteristics of children in elementary schools and portable baseball perch poles, which can be used on dirt and concrete courts. Materials and methods. This study uses qualitative and quantitative research using research and development procedures (Research and Development). a) Needs analysis; (b) Model development planning; (c) Expert validation from media experts and material experts, (d) Small group trials and revisions, and (e) Field trials and revisions. Data collection was carried out by observation, interviews and questionnaires. The data collection was adjusted to the model stages. The data collection stages were carried out in the early stages, expert tests, limited tests were carried out on small groups of 30 subjects, and field tests (field testing) of 60 subjects from two different elementary schools. In this study a closed form questionnaire was used containing questions accompanied by available answer choices so that students only need to mark the selected answer. The data obtained are grouped into frequency distributions, then the average percentage of group data is sought. Results. The research results from the first material expert validation test obtained an average of 81.94%, and the second material expert obtained 87.5% in the Very Eligible category. The small group test results obtained 90% with very good criteria, and the large group test results obtained 93% with very decent categories. Conclusions. The use of batting media that has been adapted to reduce weight, and the development of perch poles makes movement activities in small ball games more effective and efficient.